Pelatihan Pembuatan Tortilla Berbahan Dasar Jagung Sebagai Alternatif Jajanan Sehat Bagi Anak-Anak Di Desa Negeri Tongging Kec. Merek Kab. Karo, Sumatera Utara - Silvia, Cindy; Khairunnisa, Riska; Azri, Riza Nazila; Amirah, Nurul; Syahputri, Nidi; Armanda, Dicky; ., Rasyidah (CV. ITTC INDONESIA, 2024)
Corn tortillas are a healthy alternative snack made from rice flour and sweet corn, enriched with starch and simple spices. The carbohydrate content of rice flour and corn provides the energy needed for daily activities, while the fiber from corn helps maintain digestive health. Corn and seaweed bon nori used as toppings also contribute vitamins A, B and C, as well as important minerals such as magnesium, potassium, phosphorus, iodine and iron. This tortilla also contains antioxidants that support eye health and protect the body from free radicals. The aim of the community activity in making tortillas is to provide snacks that are not only delicious but also healthy, supporting the growth and development of children in the village of Negeri Tongging District. District Brand. Karo. The method used is to spread the process of making tortillas from start to finish to the community. The advantage of tortillas made from corn is of course different from tortillas made from other ingredients because corn contains a number of bioactive compounds which are believed to provide health benefits for the body. Compared to other grains, corn contains more antioxidants, such as ferulic acid, phytic acid, anthocyanins which influence the color of corn to become red or blue and purple, as well as zeaxanthin and lutein, namely carotenoids which are good for eye health.